2013
DOI: 10.3892/mmr.2013.1704
|View full text |Cite
|
Sign up to set email alerts
|

A novel four-step system for screening angiogenesis inhibitors

Abstract: Abstract. Angiogenesis exhibits a significant effect on tumor progression. Inhibiting angiogenesis may provide significant advantages over currently available therapeutics for cancer therapies thus, the development of a system of screening angiogenesis is essential. In the present study, a novel available system of screening angiogenesis inhibitors by four steps was developed. The chorioallantoic membrane (CAM), yolk sac membrane and early chick embryo blood island assay were initially performed to obtain poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…HMGA1 expression was closely correlated with the clinical stage and histological grade of patients with breast cancer and breast cancer progression in MMTV‐PyMT mice, indicating that the overexpression of HMGA1 can promote breast cancer growth. MMTV‐PyMT mice, a spontaneous breast cancer model, have been shown to exhibit distinctly identifiable stages of breast cancer progression from premalignant to malignant stages (Zhou et al, ). Moreover, MMTV‐PyMT mice are powerful tools for studying processes involved in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HMGA1 expression was closely correlated with the clinical stage and histological grade of patients with breast cancer and breast cancer progression in MMTV‐PyMT mice, indicating that the overexpression of HMGA1 can promote breast cancer growth. MMTV‐PyMT mice, a spontaneous breast cancer model, have been shown to exhibit distinctly identifiable stages of breast cancer progression from premalignant to malignant stages (Zhou et al, ). Moreover, MMTV‐PyMT mice are powerful tools for studying processes involved in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the expression of HMGA1 in human breast cancer tissues and breast cancer tissues of MMTV‐TyMT mice, a spontaneous breast cancer mouse model, as previously described (Zhou et al, ). The contributions of HMGA1 to breast cancer cell proliferation and migration were also investigated.…”
mentioning
confidence: 99%
“…Some of the best studies for screening effective drugs, including drug combinations and angiostatics, come from studies that combine faster screening models such as the CAM with other models of angiogenesis. One such study by Zhou et al describes a four-step system for screening angiogenesis inhibitors [ 78 ]. In this study, 480 compounds were tested for angiostatic activity and 28 were found to inhibit angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Allows high throughput screening [Zhou et al, 2013;Dünker and Jendrossek, 2019 Allows multiple tests per individual CAM [Bertossi et al, 1999;Deryugina, 2016] High reproducibility the visualization. As the experiments are always synchronized with the embryonic development of the chick before hatching, the duration to establish the graft only requires 14-18 days which is significantly shorter than what is usually needed for the mouse model.…”
Section: Inexpensivementioning
confidence: 99%